Magical acts and their significance at the birth of a child - Orban, Emanuel (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2023)
The birth of a child is an event that is also the subject of ethnological research. The human being, when he is born is is already the focus of attention of the family and the community, because for both groups it represents a significant change in their previous way of life. Ethnological studies confirm that, with the birth of a child, the a number of ritual ceremonies, magical acts and superstitions have been associated with childbirth since time immemorial. The aim of this contribution is to provide an overview of the magical acts that were associated with the arrival of a new member to the family. In our study, we will use the method of interpretive analysis, the purpose of which is to to capture the magical practices present at the various stages in the birth of a child such as pregnancy, childbirth, six months, the neonatal period and baptism